2021
DOI: 10.3390/gels7040169
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Degelling Thermoresponsive Hydrogel

Abstract: Responsive polymeric hydrogels have found wide application in the clinic as injectable, biocompatible, and biodegradable materials capable of controlled release of therapeutics. In this article, we introduce a thermoresponsive polymer hydrogel bearing covalent disulfide bonds. The cold aqueous polymer solution forms a hydrogel upon heating to physiological temperatures and undergoes slow degradation by hydrolytic cleavage of ester bonds. The disulfide functionality allows for immediate reductive cleavage of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Disulfide bonds are dynamically reversible covalent bonds, which are ubiquitous in organisms and play an important role in maintaining the tertiary structure of proteins and intracellular redox potentials [ 48 , 49 ]. This specific covalent bond can be rapidly transformed with mercaptan due to the influence of pH value and an oxidation reducing agent and is widely used in the preparation of self-healing hydrogels [ 50 , 51 , 52 ].…”
Section: Self-healing Hydrogel Design Strategymentioning
confidence: 99%
“…Disulfide bonds are dynamically reversible covalent bonds, which are ubiquitous in organisms and play an important role in maintaining the tertiary structure of proteins and intracellular redox potentials [ 48 , 49 ]. This specific covalent bond can be rapidly transformed with mercaptan due to the influence of pH value and an oxidation reducing agent and is widely used in the preparation of self-healing hydrogels [ 50 , 51 , 52 ].…”
Section: Self-healing Hydrogel Design Strategymentioning
confidence: 99%
“…Recently, the synthesis of hydrophobic polymers, in particular PLA, to produce thermohydrogels has been achieved without the use of a solvent, which enhances thermohydrogels' biocompatibility [165]. Furthermore, a PLA-based hydrogel was designed that might be applied as a delivery vehicle with immediate release upon contact with reducing conditions, such as tumour microenvironments [166]. The polymer solution gelled between 32 • C and 40 • C due to the decrease in polymer solubility and collapsed upon exposure to strong reducing agents due to the cleavage of the disulphide bond incorporated in the polymer structure [166].…”
Section: Hydrogelsmentioning
confidence: 99%
“…Additionally, the concentration of intracellular GSH in cancer cells is about 100–1000 times higher than that in normal cells due to rapid proliferation 18 . This characteristic has led to significant attention on GSH‐responsive polymeric carriers 19–21 Studies have shown that thioketones, thioethers, and selenium exhibit excellent responsiveness to GSH 22,23 . The use of GSH‐responsive polymeric drug delivery systems with disulfide groups has been extensively researched 24–26 .…”
Section: Introductionmentioning
confidence: 99%
“…18 This characteristic has led to significant attention on GSH-responsive polymeric carriers [19][20][21] Studies have shown that thioketones, thioethers, and selenium exhibit excellent responsiveness to GSH. 22,23 The use of GSH-responsive polymeric drug delivery systems with disulfide groups has been extensively researched. [24][25][26] Sun et al reported on a polymer PEG-SS-PCL containing a disulfide junction.…”
mentioning
confidence: 99%